DCEP-SE: A Dublin Core Application Profile for Experimental Software Engineering - Santana, Filipe A.; Cordeiro, André F. R.; OliveiraJr, Edson (Anais da Escola Regional de Engenharia de Software (ERES); 2025: Anais da IX Escola Regional de Engenharia de Software, 2025)
Experimental Software Engineering (ESE) faces persistent challenges in the standardization of metadata for artifacts, which limits the replication, comparison, and reuse of experimental results. Metadata provides a structured means to describe artifacts, thereby enhancing reproducibility; however, widely adopted standards such as Dublin Core (DC) may not adequately capture the specific requirements of ESE. To address this gap, this study proposes and validates DCEP-SE, a DC-based application profile tailored for documenting software engineering experiments. The profile was iteratively refined through the progressive exclusion of non-essential elements, resulting in a concise set of qualified terms aligned with experimental phases. DCEP-SE was applied to a real-world study, enabling systematic documentation of context, variables, and results. The profile enhances interoperability, promotes artifact reuse, and standardizes the reporting of ESE studies. Moreover, it provides a reusable methodological process for developing domain-specific metadata profiles in experimental software engineering.